2009
DOI: 10.5194/angeo-27-3645-2009
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of planetary wave type oscillations with periods of 2–20 days derived from O<sub>2</sub> atmospheric and OH(6-2) airglow observations at mid-latitude with SATI

Abstract: Abstract. The presence of planetary wave type oscillations at mid-latitudes in the mesosphere/lower thermosphere region has been investigated using airglow observations. The observations were taken with a Spectral Airglow Temperature Imager (SATI) installed at Sierra Nevada Observatory (37.06 • N, 3.38 • W) at 2900 m height. Airglow data of the column emission rate of the O 2 Atmospheric (0-1) band and of the OH Meinel (6-2) band and deduced rotational temperatures from 1998 to 2007 have been used in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…There is a 1.3 % per year relative drift between SATI and SABER intensities, the SATI signal being relatively smaller with time, probably due to faster aging. The mean SABER and SATI temperature difference is 5.6 K, which is in agreement with previous results from López-González et al (2009). Temperature differences do not strongly depend on temperature, so the slope is close to unity.…”
Section: Application To Sati-osnsupporting
confidence: 81%
See 1 more Smart Citation
“…There is a 1.3 % per year relative drift between SATI and SABER intensities, the SATI signal being relatively smaller with time, probably due to faster aging. The mean SABER and SATI temperature difference is 5.6 K, which is in agreement with previous results from López-González et al (2009). Temperature differences do not strongly depend on temperature, so the slope is close to unity.…”
Section: Application To Sati-osnsupporting
confidence: 81%
“…These studies have focused on varied topics: analysis of the impact of atmospheric waves on regional and global scales, the detection of geo-hazards, the effect of sudden stratospheric warmings (SSWs), seasonal and interannual variations, external forcing response, longterm trends, cross-validation for satellite measurements, the detection of satellite drifts and the determination of OH radiative properties (e.g., López-González et al, 2009;Cho et al, 2010;Bittner et al, 2010;French and Mulligan, 2010; M. García-Comas et al: OH layer altitude over the OSN Offermann et al, 2010;Shepherd et al, 2010a, b;French and Klekociuk, 2011;García-Comas et al, 2012;Ammosov et al, 2014;Reisin et al, 2014;Liu et al, 2015;Wüst et al, 2017, to mention just a few. ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that the periodicity was the results of the nonlinear interaction of the variations of different periods, such as the 9-day and 13.5-day variations. They might also be related to the lower-atmospheric planetary waves that propagate upward to the mesosphere and lower-thermosphere region causing changes in the ionosphere (López-González et al, 2009). In fact, Liu et al (2010) showed, using model simulations, that stationary planetary waves can modify semidiurnal tides which, in turn, produce changes in the neutral-wind dynamo and introduce periodicities in the ionospheric peak density and total-electron content that have the same periods as those of the planetary waves.…”
Section: Discussionmentioning
confidence: 99%
“…These airglow derived temperatures have been used for example for studying planetary waves with periods from days to weeks (e.g. Sivjee et al, 1994;Espy et al, 1997;Takahashi et al, 2002;Buriti et al, 2005;Höppner and Bittner, 2007;López-González et al, 2009) as well as for investigating atmospheric gravity waves with periods of several hours down to about 8 min (e.g. Gavrilov et al, 2002;Reisin and Scheer, 2004).…”
Section: Introductionmentioning
confidence: 99%